Hederagenin Shows Protective Effects Against Sodium Selenite-Induced Oxidative Stress and Cataractogenesis in Rats via Activation of Nrf2/HO-1 Pathway - Yang, Min; Meng, Li; Zhang, Zhanrong; Chen, Wenjun; Li, Yanlong (Indian Journal of Pharmaceutical Education and Research)
Background: Cataracts, a pervasive ocular condition, are defined by the progressive opacification of the crystalline lens, leading to a gradual decline in visual acuity and overall quality of life. This lens clouding obstructs the passage of light to the retina, resulting in blurred or distorted vision. Objectives: The current study was performed to investigate the protective mechanisms of hederagenin against sodium selenite-induced cataract formation in rat pups. Materials and Methods: Experimental cataract in rat pups were induced using sodium selenite, and they were treated with hederagenin at dosages of 10 and 20 mg/kg, respectively. The lens opacification, oxidative stress markers, Calcium (Ca), and Ascorbic Acid (ASA) levels were evaluated in the lens of the experimental rat pups. The levels of antioxidants, inflammatory biomarkers, and Nrf-2, HO-1, and NQO-1 were assessed in the lens of the rat pups using kits. Results: The current findings of this study shown that hederagenin treatment effectively decreased the lens opacification level, oxidative stress markers, Ca levels, and elevated the ASA levels in the lens of cataract-induced rat pups. Furthermore, the hederagenin treatment effectively increased the antioxidant concentrations, decreased the COX-2 and NF-κB levels, and increased the HO-1 and Nrf-2 levels in the lens of the cataract-induced rat pups. Conclusion: This work indicated that hederagenin effectively protected the progression of sodium selenite-induced cataractogenesis in rat pups. The findings of this work indicate that hederagenin may serve as a viable treatment option for cataract and warrants further investigation in clinical trials.
Keywords: Nrf-2/HO-1 pathway; Cataractogenesis; Cyclooxygenase-2; Hederagenin; Lens opacification.